Occupational motivation of music teachers as significant factor of social wellbeing - Gabnytė, Giedrė; Strakšienė, Diana (Social Welfare: Interdisciplinary Approach, 2014)
The article deals with the peculiarities of manifestations of music school teachers’ occupational motivation as a significant factor of social wellbeing. It presents the results of questionnaire survey of teachers: professional satisfaction estimates are given, peculiarities of collaboration of participants in the process of education are revealed, and evaluations of health, work conditions, and material interest of teachers are provided.
Keywords: social wellbeing; music teachers; occupational motivation